Hepatitis B: Report of prevalence and access to healthcare among Chinese residents in Sheffield UK - Alicia B. Vedio; Helena Ellam; Frances Rayner; Benjamin Stone; Goura Kudesia; Michael W. McKendrick; Stephen T. Green (Elsevier, 2013)
Summary: Overall prevalence of hepatitis B (HBV) in the UK is low. However, among migrants from endemic areas, prevalence has been shown to be high. Furthermore, timely diagnosis and/or referral are required prevent serious health consequences through early institution of treatment. Methods: We identified locations that would be familiar to Chinese members of the community with the objective of facilitating testing. Dried blood spot samples were collected from 229 Chinese subjects and tested for HBV and also for hepatitis C virus (HCV) infection - offering complete chronic viral hepatitis screening. Results: HBsAg was positive in 20/229 (8.7%) participants, (10 F, 10 M). Five women and one man were aware of their condition, but only one man and none of the women were under specialist care. The average length of residence in the UK for positive patients was 15 years (range 2-40).Evidence of HBV past infection, HBcAb(+)/HBsAg(−), was seen in 28/229 participants (12.2%). HCV antibody testing produced negative results in all participants.The methodology of testing was well accepted, 139/144 (95%) responded to a feedback questionnaire declaring no discomfort and 100% finding the information session useful. Conclusion: This model of outreach testing is helpful for addressing health inequalities afflicting the UK's Chinese community. Keywords: Hepatitis B, Chinese, Prevalence, Migrant health, HBV, Healthcare access